Propaganda y mitografía en el cine de la guerra civil española (1936-1939) - Sánchez Biosca, Vicente (CIC. Cuadernos de Información y Comunicación, 2007)
The Spanish civil war put on work the most advanced propaganda machinery known at that time. It was decisive the dramatic tension in- between the totalitarisms and of Nazism and Fascism with Western Democracies, but also the state of development of communication and representing media (illustrated magazines, new photographical techniques, circulation of moving images through film news). This article focus on two main aspects: first, the role played by movie-making, international and national, in the civil war, to fix some genres and subjects in war’ s representation in Western Culture (the symbolic warfare, if preferable) and the subsequent idea of the migration of images that go from one modern mass media to another. Finally it is argued the idea that the term “propaganda” in insufficient to explain the effort of the different ideologies ( Communism, Anarquism, Democracy, Nationalism) to justify themselves and to find their sense in the confrontation. In this sense we propose the term “mythography”.